The role of endocan and selected pro-inflammatory cytokines in systemic lupus erythematosus - Kamila Tokarska (Advances in Dermatology and Allergology, 2019)
Introduction: Systemic lupus erythematosus (SLE) is a multisystem inflammatory autoimmune disease with a wide spectrum of clinical manifestations. Cytokines such as interleukin-1 (IL-1) and tumor necrosis factor alpha (TNF-α) are involved in its pathogenesis. Endocan is a novel marker of endothelial dysfunction, and is likely to be engaged in pro-inflammatory processes in SLE. Material and methods : The study included 36 patients with SLE. SLEDAI-2K score was used to assess disease activity. The control group comprised 23 healthy volunteers. ELISA kits were used to asses serum concentrations of endocan, IL-1β, TNF-α, VEGF and high-sensitivity C reactive protein (hs-CRP). Results : The serum concentration of endocan was significantly higher (p<0.001) in the SLE group than in healthy individuals. A positive correlation was found between serum levels of endocan and interleukin 1β (r =0.47, p<0.05). Active SLE patients ( SLEDAI-2K score above 6 points) with elevated total cholesterol level (above 5.17 mmol/L) were found to have VEGF concentrations higher than those with normal cholesterol level (p<0.03). No other relevant relationships were found between serum concentration of endocan, other laboratory parameters, anthropometric features, activity and duration of SLE. Conclusions: Higher serum level of endocan in SLE patients indicates its possible role in the pathogenesis of the disease and reflects endothelial dysfunction. Our findings indicate that endocan could serve as a potential marker of endothelial dysfunction and a useful target for the treatment of SLE in the future.